2014
DOI: 10.1186/1478-4505-12-4
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of toxicology research productivity in Middle Eastern Arab countries during a 10-year period (2003–2012)

Abstract: BackgroundBibliometric studies are increasingly being used for research assessment by involving the application of statistical methods to scientific publications to obtain the bibliographics for each country. The main objective of this study was to analyse the research productivity originating from 13 Middle Eastern Arab (MEA) countries with articles published in toxicology journals.MethodsData from January 1, 2003 till December 31, 2012 were searched for documents with specific words in the toxicology field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 31 publications
5
100
0
Order By: Relevance
“…The USA and the UK were the most influential countries with the most publications, productive institutions and international cooperation. Bibliometric studies in other toxicological fields also demonstrated the predominance of the USA and the UK over other worldwide countries in number and quality of research output in various toxicological fields . This research activity in the field of lithium toxicity may be related to population size, economic factors, the size of the scientific community, research traditions and funding in these countries , and also the incidence of lithium toxicity or number of poison centres may play a role in research performance .…”
Section: Discussionmentioning
confidence: 99%
“…The USA and the UK were the most influential countries with the most publications, productive institutions and international cooperation. Bibliometric studies in other toxicological fields also demonstrated the predominance of the USA and the UK over other worldwide countries in number and quality of research output in various toxicological fields . This research activity in the field of lithium toxicity may be related to population size, economic factors, the size of the scientific community, research traditions and funding in these countries , and also the incidence of lithium toxicity or number of poison centres may play a role in research performance .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study is not without limitations, most of which are the same as those of studies performed in other biomedical fields [7,8,14,76]. First of all, we used ISI web of knowledge database and therefore articles published in elsewhere were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Publication activity was adjusted for Arab countries, categorized by population size and gross domestic product (GDP), which was retrieved from the online databases of the World Bank [88]. An adjustment index (AI) was calculated using the following formula: AI = [total number of publications for the country/GDP per capita of the country]*1000, where the GDP per capita = GDP/population of the country [9,89,90]. Scientific output was evaluated based on a methodology developed and used in other bibliometric studies [91][92][93].…”
Section: Methodsmentioning
confidence: 99%